Four new leaf-mining Acalyptris species from Guatemala and Belize, with new data on bionomics of Stigmella pruinosa (Lepidoptera: Nepticulidae) - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Noreika, Remigijus; Schuster, Jack (Zootaxa, 2013)
This paper describes four new species: Acalyptris basicornis Remeikis & Stonis, sp. nov., A. peteni Diškus & Stonis, sp. nov., A. caribbicus Diškus & Stonis, sp. nov. (host-plant: Lantana involucrata L., Verbenaceae), and A. statuarius Diškus & Stonis, sp. nov. Another species, Stigmella pruinosa Puplesis & Robinson, is re-described, with new distribution records in Guatemala and with the first documentation of leaf-mines on Guazuma ulmifolia Lam. (Malvaceae). All five species are illustrated with photographs of the leaf-mines, adults, and genitalia.